Optimalisasi Peningkatan Kinerja Aparatur Sipil Negara Melalui Standar Kompetensi Jabatan Pimpinan Tinggi Pratama dan Jabatan Administrator di Pemerintah Daerah Kabupaten Ogan Komering Ilir - Mauliddini, Mauliddini; Syaparman, Syaparman; Asteriniah, Femi (@-Publik: Jurnal Administrasi Publik, 2025)
The purpose of this study was to describe and analyze the optimization of performance improvement of the civil state apparatus through competence standards for primary senior leadership positions and administrator positions in the regional government of Ogan Komering Ilir. This research is qualitative research. The results of the study show that improving the performance of civil state apparatuses through competence standards for primary positions of senior leaders and administrative positions in the regional government of Ogan Komering Ilir is not optimal because there are still obstacles. These obstacles are that there are still vacancies in various agencies and that the skills and capabilities of the devices are low. Another obstacle is the lack of available resources, which leads to a minimum level of education and training for equipment. The performance level was well achieved, although not all target performance indicators were 100% achieved.